Manajemen Strategik dan Mutu Pendidikan Islam - Khori, Ahmad (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2016)
A qualified education is an education which is able to develop nation character as well as civilization. Therefore, the values of faith, obedience, piousness, virtuous acts, healthiness,knowledge, competence, creativity, self-reliance, democracy and responsibility shouldbe strengthened within educational institutions including students and stakeholders.Nowadays, most schools superficially develop some of the educational aspects, such as,cognitive dimension that is taught through memorizing and psychomotor dimensionwhich is merely a mechanistic process. Meanwhile, other dimensions, such as relationaldimension, are not handled properly. Ideally, a qualified school should be able to developcognitive dimension, not only as a memorization but also as knowledge mastery suitableto students’ capacity as well as their endowment. From this phenomenon, I tried to offera concept of implementation and development of Islamic education within strategicmanagement framework related to teaching-learning process both in formal and nonformalschools.TheaimistofortifystudentssothattheywillkeepholdingontoQur’an, Hadits,Ijma’ and Qiyas in this global era. Core concept of the strategic managementin Islamic education is indeed still novel. Therefore, it is expected that this article canbe used in broader area of Islamic education. Moreover, it is also hoped that it willpositively affect resources allotment effectiveness in order to achieve the objective ofnational education. One way is through SWOT analysis, so that institutions of theIslamic education will be able to produce well-qualified graduates who play significantroles in society.